Aprendizagens musicais na Orquestra de Teclados "Zélio Sanches Navarro": um estudo de caso - Muniz, Leíse Garcia Sanches (2018)
This research intended to understand the learning process of the students of ―Zélio Sanches Navarro Keyboards Orchestra during their musical experiences at the State Conservatory of Music "Dr. José Zóccoli de Andrade", from Ituiutaba - MG. It also aimed to describe the characteristics and musical experiences of the members, analyze the relations between the keybordists and the used repertoire, as well as the articulations and transformations caused by the involved sociocultural exchanges. The methodology used was the case study with a qualitative approach (YIN 2005; BAPTISTA, CAMPOS 2016). Based on participative observation (BREAKWELL, 2010), questionnaires and semi-structured interviews and testimonies, a naturalistic and interpretative approach was considered in the understanding of the accomplished musical practices (DENZIN, LINCOLN 2006; MARTINS, BICUDO 1989). For this purpose, the theoretical framework was based on the contextualization of the pedagogical-musical knowledge of Kraemer (2000) in the aspects of musical transmission, as well as on studies by Souza (2004) and Setton (2009), which deal with music as a total social fact, which allow us to cover a total of observable aspects in the experiences and relations of the Keyboards Orchestra as a musical and social practice. The analyzes revealed that the heterogeneity of the group favors the co-learning and the content resignification among the members, which increases the exchanges between the educative influences coming from multiple spaces. The observed musical learning dealt with musical, social and personal approaches, emphasizing the development of listening to other instruments, musical appreciation, expansion of repertoire, playing in groups, relations of respect, integration, companionship and conviviality, concentration and the overcoming of limits and inhibitions. The sense of belonging to the group causes the learning to be permeated by feelings of prestige, acceptance, personal fulfillment, elevation of self-esteem and social recognition, which makes the "Zélio Sanches Navarro" Keyboard Orchestra a place of formation and transformation that uses music as a powerful tool for democratic, supportive and inclusive education. Lastly, this study revealed a collective musical practice which instigates reflexions about group musical learning and expands the possibilities of pedagogical actuation of music as social practice.